4 th International Health Economics & Outcomes Research Conference-2025 - Organized by International Society for Pharmacoeconomics and Outcomes Research (ISPOR) India Andhra Pradesh Regional Chapter (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Raghavendra Institute of Pharmaceutical Education and Research (RIPER)-Autonomous, Chiyyedu Post, Anantapur, India 25 & 26 April, 2025 Andhra Pradesh, India